Community Service on Enhancing Digital Literacy through Canva and Wordwall Training at SDN 1 Menteng Palangka Raya - Norfaujiah, Norfaujiah; Hasanah, Uswatun; Fitrianur, Watik; Qamariah, Zaitun; Yuliani, Hadma; M. Sabrina, M. Sabrina (PT. Amirul Bangun Bangsa, 2025)
This collaborative Community Service activity aims to enhance digital literacy among elementary school students by developing interactive teaching materials based on Canva and Wordwall at SDN 1 Menteng. The activity was carried out using the ABCD (Asset-Based Community Development) approach, which emphasizes utilizing assets and potential within the community. The activity stages included socialization, training, mentoring, and a simple evaluation of the use of digital learning media. The results of this activity show that the students of PGMI could design and use interactive teaching materials more engagingly and effectively. Through this program, it is expected that the quality of learning in elementary schools can improve, and the students' digital competencies as future teachers will develop further to face the challenges of education in the digital era.